Pengaruh Beban Kerja dan Work-Life Balance Terhadap Turnover Intention pada karyawan PT. OTO Group Pontianak dengan Stres Kerja sebagai Variabel Mediasi - Anugrah, Sultan Ridho; G, Giriati; Ramadhan, Rizani; Kalis, Maria Christiana Iman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research seeks to examine the impact of workload and work-life balance on employees' turnover intention at PT. OTO Group Pontianak, with job stress acting as a mediating factor. Utilizing a quantitative approach, the study applies PLS-SEM analytical methods to data gathered from 50 respondents through a structured questionnaire. The findings reveal that a high workload significantly contributes to increased job stress and a higher intention to leave, while a strong work-life balance significantly reduces both. Moreover, the findings indicate that job stress acts as a partial bridge linking both workload and work-life balance to employees' intentions to resign. This emphasizes the importance of optimizing task distribution and fostering policies that support a healthy division between professional and personal life. As a strategic response, organizations are advised to prioritize managing employee workloads and promoting work-life harmony to alleviate stress and discourage voluntary departures.